Data and data privacy impact assessments in the context of AI research and practice in the UK - Gilbert, Fiona J.; Palmer, Jo; Woznitza, Nick; Nash, Jonathan; Brackstone, Carla; Faria, Lisa; Dunbar, J. Kevin; Hogg, Henry David Jeffry; Liu, Xiaoxuan; Denniston, Alastair K. (Frontiers in Health Services, 2025)
Artificial intelligence (AI) projects in healthcare research and practice require approval from information governance (IG) teams within relevant healthcare providers. Navigating this approval process has been highlighted as a key challenge for AI innovation in healthcare by many stakeholders focused on the development and adoption of AI. Data privacy and impact assessments are a part of the approval process which is often identified as the focal point for these challenges. This perspective reports insights from a multidisciplinary workshop aiming to characterise challenges and explore potential solutions collaboratively. Themes around the variation in AI technologies, governance processes and stakeholder perspectives arose, highlighting the need for training initiatives, communities of practice and the standardization of governance processes and structures across NHS Trusts.